Hubungan Antara Perhatian Orang Tua dengan Motivasi Belajar Siswa di SD Negeri 12 Semanan Kecamatan Kalideres - Fathiyah Ummul Atikah; Ainur Rosyid (Journal on Education, 2024)
This research aims to determine the relationship between parental attention and student learning motivation at SDN 12 Semanan, Kalideres District. This study uses a qualitativeapproach. The sample from this population uses the solvin formula technique, in collecting data using a questionnaire. The results of this study concluded that there is a good relationship between Parental Attention and Student Learning Motivation.